2009
DOI: 10.1007/s00787-009-0059-y
|View full text |Cite
|
Sign up to set email alerts
|

Childhood loneliness as a predictor of adolescent depressive symptoms: an 8-year longitudinal study

Abstract: Childhood loneliness is characterised by children's perceived dissatisfaction with aspects of their social relationships. This 8-year prospective study investigates whether loneliness in childhood predicts depressive symptoms in adolescence, controlling for early childhood indicators of emotional problems and a sociometric measure of peer social preference. 296 children were tested in the infant years of primary school (T1 5 years of age), in the upper primary school (T2 9 years of age) and in secondary school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
220
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(242 citation statements)
references
References 58 publications
11
220
0
11
Order By: Relevance
“…For example, the significant links between loneliness and a wide range of mental health difficulties (e.g., depression, anxiety, suicidal ideation, self-injury, and alcohol and substance misuse) and physical health issues (e.g., poor immune and cardiovascular functioning, sleep deprivation) have been consistently demonstrated in adolescents (Heinrich & Gullone, 2006;Shevlin, Murphy, Mallet, Stringer, & Murphy, 2013). Cross-sectional and longitudinal studies have found that loneliness is significantly correlated with depressive symptoms across time in children and adolescents (Hall-Lande, Eisenberg, Christenson, & NeumarkSztainer, 2007;Nangle, Erdley, Newman, Mason, & Carpenter, 2003;Qualter, Brown, Munn, & Rotenberg, 2010;Rotenberg et al, 2004;Vanhalst et al, 2012). Mahon et al (2006) reported that the correlation between loneliness and depressive symptoms in adolescents was in the range of a large effect size (r = 0.61 to 0.62).…”
Section: The Relationship Between Loneliness and Depressive Symptomsmentioning
confidence: 99%
“…For example, the significant links between loneliness and a wide range of mental health difficulties (e.g., depression, anxiety, suicidal ideation, self-injury, and alcohol and substance misuse) and physical health issues (e.g., poor immune and cardiovascular functioning, sleep deprivation) have been consistently demonstrated in adolescents (Heinrich & Gullone, 2006;Shevlin, Murphy, Mallet, Stringer, & Murphy, 2013). Cross-sectional and longitudinal studies have found that loneliness is significantly correlated with depressive symptoms across time in children and adolescents (Hall-Lande, Eisenberg, Christenson, & NeumarkSztainer, 2007;Nangle, Erdley, Newman, Mason, & Carpenter, 2003;Qualter, Brown, Munn, & Rotenberg, 2010;Rotenberg et al, 2004;Vanhalst et al, 2012). Mahon et al (2006) reported that the correlation between loneliness and depressive symptoms in adolescents was in the range of a large effect size (r = 0.61 to 0.62).…”
Section: The Relationship Between Loneliness and Depressive Symptomsmentioning
confidence: 99%
“…These constructs are strongly associated, although they are different (see Lasgaard, Goossens, & Elklit, 2010;Nangle et al, 2003;Qualter et al, 2010). Furthermore, there is evidence that depressive symptoms are associated with both peer rejection (e.g., Boivin, Poulin, & Vitaro, 1994), and sensitivity to rejection (Dineen, & Hadwin, 2004;Quiggle et al, 1992).…”
Section: Limitations Of Previous Work On Hsthmentioning
confidence: 99%
“…Guided by this approach, we examined whether the relation between loneliness and hypervigilance to social threat is curvilinear, specifically quadratic, and thus discontinuous. The research specifically examined whether there is a point Running Head: LONELINESS AND HYPERVIGILANCE TO SOCIAL THREAT 8 on the child loneliness scale where there is an accompanying change in behaviour, such that there is elevated vigilance to social threat.Another important consideration is the association between loneliness and depression.These constructs are strongly associated, although they are different (see Lasgaard, Goossens, & Elklit, 2010;Nangle et al, 2003;Qualter et al, 2010). Furthermore, there is evidence that depressive symptoms are associated with both peer rejection (e.g., Boivin, Poulin, & Vitaro, 1994), and sensitivity to rejection (Dineen, & Hadwin, 2004;Quiggle et al, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, chronic loneliness during adolescence predicts poor physical health (Harris, Qualter, & Robinson, 2013;Qualter, Brown, et al, 2013) and increases in anxiety and depressive symptoms (Qualter, Brown, Munn, & Rotenberg, 2010;Qualter, Brown et al, 2013;Schinka, Van Dulmen, Bossarte, & Swahn, 2012;Schinka et al, 2013;Vanhalst, Goossens, Luycks, Scholte, & Engels, 2013), with those RUNNING HEAD: LONELINESS AND EMOTIONAL INTELLIGENCE 5 highest on loneliness showing the biggest gains in depressive symptoms over time (Ladd & Ettekal, 2013). There is also an association between suicidal ideation and loneliness during childhood and adolescence (Schinka et al, 2012(Schinka et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%